2016
DOI: 10.1016/j.jgeb.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Direct somatic embryogenesis of Malaxis densiflora (A. Rich.) Kuntze

Abstract: A protocol for induction of direct somatic embryogenesis and subsequent plant regeneration for the medicinally important and endangered plant of Malaxis densiflora has been developed for the first time. In the present study, in vitro seed derived protocorm explants were cultured on half strength Murashige and Skoog (MS) medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4-D), Picloram and Dicamba individually and in combination with cytokinins BAP, TDZ and Kn for its effectiveness to induce the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…For DSE, the treatment with the combination of 2,4-D and TDZ showed a much higher induction rate of globular embryos than the application of 2,4-D alone, suggesting that a certain ratio of 2,4-D and TDZ might play a significant role in the process of DSE and that phytohormones are necessary for the maintenance of DSE in C. oleifera . Such combined favorable influence of auxin and cytokinins is in accordance with reports in Malaxis densiflora ( Mahendran and Bai, 2016 ), date palm ( Baharan and Mohammadi, 2018 ), and Coelogyne cristata ( Naing et al, 2011 ). Conversely, the addition of 2,4-D alone was not favorable for DSE in Oncidium ( Chen et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For DSE, the treatment with the combination of 2,4-D and TDZ showed a much higher induction rate of globular embryos than the application of 2,4-D alone, suggesting that a certain ratio of 2,4-D and TDZ might play a significant role in the process of DSE and that phytohormones are necessary for the maintenance of DSE in C. oleifera . Such combined favorable influence of auxin and cytokinins is in accordance with reports in Malaxis densiflora ( Mahendran and Bai, 2016 ), date palm ( Baharan and Mohammadi, 2018 ), and Coelogyne cristata ( Naing et al, 2011 ). Conversely, the addition of 2,4-D alone was not favorable for DSE in Oncidium ( Chen et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
“…Phytohormones are another key influencing factors for SE. Most plant species undergoing SE are dependent on the powerful action of auxin and cytokinin, especially 2,4dichlorophenoxyacetic acid (2,4-D) which regulates and balances endogenous auxin levels (Illyas Ahmad et al, 2013;Mahendran and Bai, 2016;Keshvari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, plant regeneration via direct somatic embryogenesis had been successfully established in various orchids including Dendrobium (Chung et al 2005), Epipactis (Moradi et al 2017), Malaxis (Mahendran and Bai 2016), Phalaenopsis (Chen and Chang 2006; Gow et al 2010; Feng and Chen 2014), Rhynchostylis (Islam and Bhattacharjee 2015) and also a Tolumnia related genus, Oncidium (Chen et al 1999; Chen and Chang 2002; Su et al 2006; Hong et al 2008a, b). In these previous studies, cytokinins, especially thidiazuron, were found to be effective to induce direct somatic embryogenesis from the leaf explants (Chen et al 1999; Chen and Chang 2002; Su et al 2006; Hong et al 2008a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins are known to stimulate cells and, as such, they are also suitable candidates for induction of somatic embryogenesis and caulogenesis (Deo et al, 2010). For example, thidiazuron (TDZ) has been reported to stimulate in vitro somatic embryogenesis (Srangsam and Kanchanapoom, 2003;Mithila et al, 2003;Lin et al, 2004;Chen and Chang, 2006;Mahendran and Bai, 2016;Mose et al, 2017). Cytokinins have been reported to induce callus formation in cassava (Faye et al, 2015;Mongomake et al, 2015) and in Vitex doniana (Dadjo et al, 2015).…”
Section: Effects Of Different Concentrations Of Cytokinins and Auxinsmentioning
confidence: 99%